Hypoxia-inducible factor as a transcriptional factor regulating gene expression in cancer cells - Dondajewska, Ewelina; Suchorska, Wiktoria (Contemporary Oncology/Współczesna Onkologia, 2011)
Hypoxia is a commonly occurring event in solid tumours. It triggers specific and non-specific mechanisms enabling the cell to adapt to oxygen deprivation. The most important role in this process is played by hypoxia-inducible factor-1 (HIF-1), which acts as a transcription factor regulating gene expression in hypoxic cells and is overexpressed in most solid tumours. It controls key aspects of cancer biology, which include promoting angiogenesis and erythropoiesis, maintenance of stem cell pools, immortalization, switch to anaerobic metabolism, and promoting cell survival and invasion. HIF-1 itself can be regulated via a number of oxygen-dependent or independent mechanisms, some of which are still poorly understood. It is of great importance to know exactly how HIF-1 is expressed and stabilized, as only this way can efficient HIF-1 inhibitors be provided. This review summarizes mechanisms of HIF-1 control and evaluates anticancer agents based on HIF-1 inhibitors known to date.